2021
DOI: 10.3390/polym13020197
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Surface-Modified PAN Nanofibrous Membranes for Efficient Oil–Water Emulsion Separation

Abstract: In order to protect the environment, it is important that oily industrial wastewater is degreased before discharging. Membrane filtration is generally preferred for separation of oily wastewater as it does not require any specialised chemical knowledge, and also for its ease of processing, energy efficiency and low maintenance costs. In the present work, hybrid polyacrylonitrile (PAN) nanofibrous membranes were developed for oily wastewater filtration. Membrane surface modification changed nitrile groups on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Similar results have been observed before [ 20 , 29 ]. It was observed that NaOH treatment exhibited swelling of PAN membranes, resulting in a pore diameter reduction [ 30 , 31 ]. The NaOH cleaning agent caused hydrolysis of nitrile groups on the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been observed before [ 20 , 29 ]. It was observed that NaOH treatment exhibited swelling of PAN membranes, resulting in a pore diameter reduction [ 30 , 31 ]. The NaOH cleaning agent caused hydrolysis of nitrile groups on the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
“…UF effluent needs excessive treatment, hence remained concentrate or backwash flushes (slurry) are directed to incinerators for further COD decrease to deal with environmental regulations. [178] The EV treatment unit shows the highest capital cost and electrical demand, which the highest reduction to COD, together with the highest payback time (1.14 years) and lowest present net value. [190] The least technology-consuming expense is UF, with the highest net present value, and the lowest reimbursement time (0.22 years), compared with EC that needs 0.89 years as compensation time.…”
Section: Economics Of Membrane Separation Of Oil In Water Emulsionsmentioning
confidence: 98%
“…The optimized electrodes were afterwards tested in H 2 and CH 4 fuel gases where they showed good thermal and redox cycling stability [ 211 ]. Besides this type of composite [ 212 , 213 ], other material systems as anodes for solid oxide fuel cells are, e.g., Ni-coated yttria-stabilized zirconia nanofiber mats [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ...…”
Section: Fuel Cellsmentioning
confidence: 99%
“…Typical applications of electrospun nanofiber mats can be found in the areas of biotechnology and biomedicine [ 26 , 27 , 28 , 29 ], implant scaffolds [ 30 ], micropollutant elimination [ 31 ], nanoparticle delivery [ 32 ], oil/water separation [ 33 , 34 ], air and water filtration [ 35 , 36 , 37 , 38 ], and electrochemical cells [ 39 ]. This review gives an overview of the aforementioned kinds of electrochemical cells in which electrospun nanofiber mats are applied.…”
Section: Introductionmentioning
confidence: 99%